Royal childhood and child kingship boy kings in England, Scotland, France and Germany, c.1050-1262 - Ward, Emily Joan ca. 20./21. Jh (Cambridge University Press, 2022)
Refining adult-focused perspectives on medieval rulership, Emily Joan Ward exposes the problematic nature of working from the assumption that kingship equated to adult power. Children's participation and political assent could be important facets of the day-to-day activities of rule, as this study shows through an examination of royal charters, oaths to young boys, cross-kingdom diplomacy and coronation. The first comparative and thematic study of child rulership in this period, Ward analyses eight case studies across northwestern Europe from c.1050 to c.1250. The book stresses innovations and adaptations in royal government, questions the exaggeration of political disorder under a boy king, and suggests a ruler's childhood posed far less of a challenge than their adolescence and youth. Uniting social, cultural and political historical methodologies, Ward unveils how wider societal changes between the eleventh and thirteenth centuries altered children's lived experiences of royal rule and modified how people thought about child kingship
Title from publisher's bibliographic system (viewed on 18 Aug 2022)
Royal Childhood and Child Kingship -- Children and Kingship in the Early and Central Middle Ages -- Woe to Thee, O Land? Models of Child Kingship -- Familial Education : Preparing Boys to be Kings -- Loyalty, Diplomacy and (Co-)Kingship : Preparing Political Communities -- The Royal Deathbed : Preparing for Child Kingship -- Guardianship, Regency and Legality -- Adapting and Collaborating : Child Kingship and Royal Rule -- Feasting Princes? Violence, Conflict and Child Kingship -- Entering Adolescence : Knighting, Seals and Royal Maturity -- Re-Thinking Child Kingship, c.1050-1262
Keywords: Geschichte 1050-1262; Child kings and rulers / Europe / History / To 1500; Kings and rulers, Medieval; Kind; Herrschaft; König; Europe / Politics and government / 476-1492; Europe / Kings and rulers / Succession; Deutschland; Frankreich; Schottland; England; Hochschulschrift